The Effectiveness of BBC Podcast in Teaching Listening Comprehension at Junior High School - Ramadhan, Muhammad Arfan; Hamidiyah, Aisyah; Aisah, Siti (Journal of Linguistics, Literacy, and Pedagogy, 2023)
The aim of the research is to investigate the effectiveness of the use of BBC Podcast in teaching listening comprehension for 9th grade students. Using quantitative research by applying true experimental design, this study has two groups (Experimental and Control) with 30 (thirty) students in each group. The instruments in this study are the pretest and posttest. The item tests were tested the validity and the reliability using the IBM SPSS Statistics 25 application with the Pearson Moment Product formula. Valid and reliable test items were used for the pre-test and post-test given to the experimental and control classes. In testing the hypothesis, the researcher used paired sample t-test as formula. Based on the results of the calculations, the value of sig from both groups are 0.000. and 0.000, because 0.000 & 0.000 < 0.05, it can be concluded that Ha is accepted, and Ho is rejected. It indicates the use of BBC Podcast is effective to improve students’ listening comprehension at 9th grade students.